Understanding Of Nepalese Patients With Vitiligo About Their Disease - S Agrawal; A Kumar; PM Shyngwa (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Vitiligo, a pigmentary disorder, may influence considerably patients’ health-related quality of life (QoL) and psychological wellbeing. Previous reports indicated that the patients' illness understandings influence adherence behaviors and actions in various chronic dermatological conditions.